2005
DOI: 10.5465/amj.2005.18803926
|View full text |Cite
|
Sign up to set email alerts
|

Leading from Within: The Effects of Emotion Recognition and Personality on Transformational Leadership Behavior

Abstract: Do people's self-views matter? Self-concept and self-esteem in everyday life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
359
3
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(393 citation statements)
references
References 52 publications
11
359
3
4
Order By: Relevance
“…Many studies have demonstrated the effectiveness of TL behavour in organizations [32] but there is a relative lack of research regarding the antecedents of these behaviours [45]. Previous studies link it to biographical background factors [4], intelligence [2], psychological factors [13], gender [34], and leader fit [26], but in the overall the capacity of these individual differences to predict TL has been inconclusive and as a consequence the suggestion that other unexplored factors such as EI may play a prominent role in predicting TL behaviours [38] still holds.…”
Section: Problem Statementmentioning
confidence: 99%
“…Many studies have demonstrated the effectiveness of TL behavour in organizations [32] but there is a relative lack of research regarding the antecedents of these behaviours [45]. Previous studies link it to biographical background factors [4], intelligence [2], psychological factors [13], gender [34], and leader fit [26], but in the overall the capacity of these individual differences to predict TL has been inconclusive and as a consequence the suggestion that other unexplored factors such as EI may play a prominent role in predicting TL behaviours [38] still holds.…”
Section: Problem Statementmentioning
confidence: 99%
“…Meeting targets set for a team is obviously one that gladdens the heart of all managers and supervisors. Rubin et al [18] also observed from similar studies that when teams meet or exceed targets set them the organization is surely en-route to meeting corporate objectives. Fiedler et al [19] explain further that continuous meeting of target goes a long way to strengthen the operational existence of the organization.…”
Section: Discussion Of Findingsmentioning
confidence: 76%
“…[30,37] Leaders skilled at perceiving and understanding a situation from another's point of view are also more likely to be rated by followers as transformational in leadership style. [38] Emotional intelligence further requires using an understanding of others' emotions effectively and appropriately.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Furthermore, positive affect which is highly related to extraversion, and agreeableness, which is characterized as being cooperative, warm, and friendly, [28] are both positive predictors of TL. [30] …”
Section: Individual Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation